The microstructure and texture effects on fatigue behavior of AZ31B magnesium induced by pre-strain along radial direction - Guosheng Duan; Jinze Du; Linghui Song; Wenhan Jin; Naifu Zou; Xinghao Du (Journal of Materials Research and Technology)
In this study, compressional pre-strain was conducted on fatigue samples extracted from the AZ31B rod along the radial direction (RD), leading to the alteration of microstructure and texture, of which the impact on ratcheting behavior and fatigue life under stress-controlled cyclic loading were investigated and discussed. The results demonstrated that with increasing pre-compression strain, the fatigue life increased and then decreased. The fatigue life was the longest when subjected to 2% pre-compression strain. This was primarily attributed to strain hardening caused by accumulation of dislocations and an appropriate amount of residual extension twins in the deformed structure. When pre-strain exceeds 4%, fatigue life were shortened as compared with that free of compressional pre-strain. In this case, the residual twins with large volume accelerate fatigue failure, thus reducing fatigue life. These findings provide valuable insights for the processing and application of magnesium alloys.